2013
DOI: 10.1002/anie.201209317
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Intramolecular ipso‐Friedel–Crafts Alkylation of Phenols and Indoles: Rearomatization‐Assisted Oxidative Addition

Abstract: Scheme 4. Proposed reaction mechanism.Scheme 5. Derivatization of 2 a and 3 a. mCBPA = meta-chloroperbenzoic acid, PMHS = poly(methylhydroxysilane).Scheme 6. The mode of oxidative addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Therefore, when electrond ensity is transferred from the aromatic core to the empty p-orbital of the vinyl cation, ab ond will establish in the ipso positionrather than the meta,ifthe penalty for the formation of the four-membered ring in D is not too high (see Scheme 3). [14] In other words, the process of "attacking" the vinyl cation is the same leading to 7 or the four-membered ring containing D in that it simply diverges at some point to form the more stable product, which is the four-membered ring containing D in this case, due to the destabilizing effect of the HNTos/OH in the Wheland intermediate on the way to 7. This process, in fact, is highly analogous to the first step in an arene 1,2-shift in ac lassical Wagner-Meerweinr eaction, which proceeds throught he three-membered phenonium ion C. [15] This rationalizes why an F-C reaction, if occurring, is selective for pathway aoverc,but why is it favored over adirect cyclization of the initially formed vinyl cation with the nitrogen nucleophile (pathwayb)?…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, when electrond ensity is transferred from the aromatic core to the empty p-orbital of the vinyl cation, ab ond will establish in the ipso positionrather than the meta,ifthe penalty for the formation of the four-membered ring in D is not too high (see Scheme 3). [14] In other words, the process of "attacking" the vinyl cation is the same leading to 7 or the four-membered ring containing D in that it simply diverges at some point to form the more stable product, which is the four-membered ring containing D in this case, due to the destabilizing effect of the HNTos/OH in the Wheland intermediate on the way to 7. This process, in fact, is highly analogous to the first step in an arene 1,2-shift in ac lassical Wagner-Meerweinr eaction, which proceeds throught he three-membered phenonium ion C. [15] This rationalizes why an F-C reaction, if occurring, is selective for pathway aoverc,but why is it favored over adirect cyclization of the initially formed vinyl cation with the nitrogen nucleophile (pathwayb)?…”
Section: Resultsmentioning
confidence: 97%
“…33 Mechanistic studies have shown that, in the first instance, oxidative addition of palladium(0) to 92 generates palladacycle 94, which undergoes reductive elimination to allene 95. At that point, rearomatization-assisted oxidative addition of palladium(0) to 95 affords  3 - The authors discovered that the same reaction conditions could be readily applied to the dearomatization reaction of indoles 97, installing a quaternary all-carbon center in spirocyclic indolenines 98 (Scheme 21).…”
Section: Scheme 16 Tandem Michael Addition / Cyclizationmentioning
confidence: 99%
“…At that point, rearomatization-assisted oxidative addition of palladium(0) to 95 affords  3 - The authors discovered that the same reaction conditions could be readily applied to the dearomatization reaction of indoles 97, installing a quaternary all-carbon center in spirocyclic indolenines 98 (Scheme 21). 33 Overall, several tryptamine derivatives 97 were tested and the desired transformation resulted in spirocycles 98a-c in good yields. The reactions discussed so far utilized substrates in which one of the nucleophiles is strategically tethered to the propargylic electrophile so that the order of addition of nucleophiles can be controlled by relying on the much faster rate of intramolecular cyclization.…”
Section: Scheme 16 Tandem Michael Addition / Cyclizationmentioning
confidence: 99%
“…3). 12 When tryptamine-derived carbonates were used, this reaction produced spiroindoles bearing an azepine moiety. Immediately after our communication in 2014, 13 the groups of Rawal 14a and You 14b M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Tetrahedron 2 independently reported the intermolecular reactions of indolebased dual nucleophiles and propargyl carbonates as general strategies for the synthesis of spiroindoles (eq.…”
Section: Introductionmentioning
confidence: 99%